ALGORITHM FOR CREATING STRUCTURED DIAGRAMS OF AUTOMATIC CONTROL SYSTEMS - Abdullayev, Hakim (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract. As a unique approach to the research of automatic control systems, the algorithm for creating structural schemes, which is one of the forms of their mathematical models, is described. An example of the use of this algorithm is the structure of the automatic control system of the greenhouse temperature. Objective.In this work, the object of research is the automatic control system, and the subject of research is the structural scheme of this system. Methods.Systematic analysis was used as a research method in this work. According to the systematic analysis, the automatic control system is divided into parts, and the functions of the parts are shown in the structure. Results.It is shown that if the automatic control system is divided into parts, i.e. elements, their mathematical description becomes easier. As a result of the work, an algorithm for creating structural schemes of automatic control systems is presented. Conclusion. In order to create a structural scheme of the automatic control system, it is necessary to differentiate and separate the elements of this system from each other in different ways; signs of the functional blocks of the management system were distinguished.